2008
DOI: 10.1007/s00381-008-0723-4
|View full text |Cite
|
Sign up to set email alerts
|

Modulating effect of apolipoprotein E polymorphisms on secondary brain insult and outcome after childhood brain trauma

Abstract: Different APO E alleles may potentially affect cerebral ischaemic tolerance differently in children after brain trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…By contrast, the paediatric TBI literature has shown that APOE4 is both positively and negatively associated with neurocognitive outcomes 53 64–68. In children with TBI, possession of the APOE4 allele was associated with lower Glasgow Coma Scores and more severe injury, as well as a negative early response to injury 68. In another TBI study, an association between APOE4 and unfavourable outcome was observed in a cohort of patients under the age of 16 50.…”
Section: Discussionmentioning
confidence: 90%
“…By contrast, the paediatric TBI literature has shown that APOE4 is both positively and negatively associated with neurocognitive outcomes 53 64–68. In children with TBI, possession of the APOE4 allele was associated with lower Glasgow Coma Scores and more severe injury, as well as a negative early response to injury 68. In another TBI study, an association between APOE4 and unfavourable outcome was observed in a cohort of patients under the age of 16 50.…”
Section: Discussionmentioning
confidence: 90%
“…In 2012, Kurowski reviewed the few existing studies and combined the results of three studies [107][108][109] that used the Glasgow Outcome Scale. 110 In the combined sample (252 children), the risk of poor clinical outcomes after 6-12 months was over twofold higher in APOE ε4 carriers than in noncarriers (19% versus 9%).…”
Section: Apolipoprotein Ementioning
confidence: 99%
“…Nevertheless, other studies also failed to find main effects of APOE on outcomes following pediatric TBI (Lo et al, 2009; Quinn et al, 2004), and future work should focus on explaining these mixed results. The finding that APOE e4 status moderated associations between parenting style and adaptive outcomes highlights the importance of considering the family environment when examining influences of genetic factors on pediatric TBI outcomes.…”
Section: Discussionmentioning
confidence: 90%